Uso de las plataformas virtuales y su optimización de los procesos secretariales de la Unidad Educativa 11 de Octubre - Paredes Funes, Karla Viviana (2019)
This scrutiny was carried out in the Educational Unit October 11 of the canton Urdaneta on the topic use of virtual platforms and its optimization of the secretarial processes of the "educational unit October 11", in which various processes were carried out to demonstrate the use of software applied to the organizational strategy of this public entity. For the outcome of this case study, the way in which the secretaries are handled is not correct due to the shortcomings that administrative processes have delayed, an extensive bibliographic consultation, consultations on the web pages and specialists in the subject where they are He found valuable information that was chosen and accepted to develop theoretical support. Then an observation guide was applied to control the processes that were carried out and then the interviews were applied to the different secretaries, bosses and users of the institution, in which the causes and possible effects were specified. For this reason the different processes with such a serious problematic situation were able to verify the results to present a solution which is addressed to the secretary who indicated that the secretary does not update their knowledge or know what it is about the use and management of the virtual platform for a good effective and efficient work performance, both for her and for the institution of the Education Unit “October 11” effective and efficient